Real-world effectiveness of palbociclib plus fulvestrant in advanced breast cancer - Cardoso Borges, Fábio (2022)
Funding Information: We have read the journal's policy and the authors of this manuscript have the following competing interests: ARF reports travel grants from Roche and advisory board fees from Daiichi Sankyo, Gilead, Merck Sharp & Dohme, Novartis and Roche, outside the submitted work. DMB reports travel grants from LEO Farmacêuticos, Merck Sharp & Dohme, Ipsen, Janssen, Roche, and Novartis, advisory board fees from Janssen, Pfizer, Merck Sharp & Dohme, Angelini, AstraZeneca, and Novartis, and institutional grants from F. Hoffmann-La Roche, outside the submitted work. The other authors have declared that no competing interests exist. Funding Information: The authors acknowledge the RON network that cooperated in providing up-to-date information on cases diagnosed and treated with the drug of interest (participating institutions: Centro Hospitalar Universit?rio de S?o Jo?o, Centro Hospitalar Universit?rio Lisboa Norte, Centro Hospitalar Universit?rio do Algarve, Hospital de Braga, Centro Hospitalar e Universit?rio de Coimbra, Centro Hospitalar de Tr?s-os-Montes e Alto Douro, Hospital Central do Funchal, Centro Hospitalar de Vila Nova de Gaia/Espinho, Centro Hospitalar Lisboa Ocidental, Hospital Garcia de Orta, Centro Hospitalar Universit?rio Lisboa Central, Hospital Distrital de Santar?m, Centro Hospitalar de Entre o Douro e Vouga, Hospital da Senhora da Oliveira Guimar?es, Centro Hospitalar de Set?bal, Centro Hospitalar e Universit?rio do Porto, Centro Hospitalar Tondela Viseu, Hospital do Esp?rito Santo de ?vora, Centro Hospitalar Barreiro Montijo, Hospital Beatriz ?ngelo, Hospital do Santo Esp?rito da Ilha Terceira, Hospital do Divino Esp?rito Santo de Ponta Delgada, Hospital Pedro Hispano ? ULS Matosinhos, Hospital do Litoral Alentejano ? Santiago do Cac?m ? ULS Litoral Alentejano, Centro Hospitalar do Oeste, Centro Hospitalar M?dio Tejo, Hospital Jos? Joaquim Fernandes ? Beja ? ULS Baixo Alentejo, Centro Hospitalar Universit?rio da Cova da Beira, Centro Cl?nico Champalimaud, Hospitais CUF, Hospitais da Luz, Hospitais dos Lus?adas, Hospital Particular do Algarve). Publisher Copyright: © 2022 The Authors